Coevolution of Saccharomyces cerevisiae and Lactobacillus plantarum : engineering interspecies cooperation - Du Toit, Sandra Christine (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.